"Thoughtlessness". Its Rare Meaning Enters The Times - Redaktion, U.L. / (HannahArendt.net, 2006)
Mary McCarthy in a letter to Hannah Arendt, June 9, 1971; Benedict Carey, in: The New York Times, as published by Süddeutsche Zeitung, February 14, 2005, in his article “Science Tries to Classify Savage Acts”.